2022
DOI: 10.1155/2022/1050029
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Color Doppler Ultrasound Combined with Magnetic Resonance Imaging in Placenta Accreta

Abstract: In order to improve the diagnostic value of color Doppler ultrasonography in placenta accreta and make the diagnosis more accurate, a method to detect placenta accreta by combining color Doppler ultrasonography and magnetic resonance is proposed. The patients with placenta accreta were selected for color Doppler ultrasonography and MRI examination. Kappa test was used to analyze the consistency between the results of ultrasound and MRI examination alone and combined diagnosis and pathological examination resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…BID was reported as a crucial mediator in cell growth. 30 , 31 In addition, BID could act as a promoter in cell apoptosis. 32 In this study, BID was found to be the downstream target of miR-26a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…BID was reported as a crucial mediator in cell growth. 30 , 31 In addition, BID could act as a promoter in cell apoptosis. 32 In this study, BID was found to be the downstream target of miR-26a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasound and MRI are reported to be effective in the diagnosis of placenta accreta spectrum. 8 , 9 Moreover, the involvement of a multidisciplinary team and a pre-planned procedure leads to an optimal outcome. 10 In this study we aimed to present a case of placenta percreta where we have performed ultrasound-guided transfundal vertical uterine incision to deliver a healthy fetus and subsequent cesarean hysterectomy.…”
Section: Introductionmentioning
confidence: 99%
“…
This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.
…”
mentioning
confidence: 99%